Postoperative outcome of caesarean sections and other major emergency obstetric surgery by clinical officers and medical officers in Malawi - Chimbiri Agnes; Kamwendo Francis; Pereira Caetano; Chilopora Garvey; Malunga Eddie; Bergström Staffan (BMC, 2007)
Abstract Background Clinical officers perform much of major emergency surgery in Malawi, in the absence of medical officers. The aim of this study was to validate the advantages and disadvantages of delegation of major obstetric surgery to non-doctors. Methods During a three month period, data from 2131 consecutive obstetric surgeries in 38 district hospitals in Malawi were collected prospectively. The interventions included caesarean sections alone and those that were combined with other interventions such as subtotal and total hysterectomy repair of uterine rupture and tubal ligation. All these surgeries were conducted either by clinical officers or by medical officers. Results During the study period, clinical officers performed 90% of all straight caesarean sections, 70% of those combined with subtotal hysterectomy, 60% of those combined with total hysterectomy and 89% of those combined with repair of uterine rupture. A comparable profile of patients was operated on by clinical officers and medical officers, respectively. Postoperative outcomes were almost identical in the two groups in terms of maternal general condition - both immediately and 24 hours postoperatively - and regarding occurrence of pyrexia, wound infection, wound dehiscence, need for re-operation, neonatal outcome or maternal death. Conclusion Clinical officers perform the bulk of emergency obstetric operations at district hospitals in Malawi. The postoperative outcomes of their procedures are comparable to those of medical officers. Clinical officers constitute a crucial component of the health care team in Malawi for saving maternal and neonatal lives given the scarcity of physicians.